An approach to cyber resilience of critical information infrastructures - Kashaija Joel; Massis Khader; Onuoha David Nwaezeudo (ХНУРЕ, 2021)
The paper is devoted to an approach to cyber resilience of Critical Information Infrastructures. The cyber resilience of networked services becomes especially important because in many cases such services will increasingly be offered by mission-critical applications. They will need guarantees above and beyond the ‘best effort’ that has initially been considered acceptable for applications provided by conventional networks. Moreover, mission-critical networks must continue to operate during any disaster and protect sensitive information and guard against attacks.
Keywords: Cyber resilience; Critical Information Infrastructures; Mission-critical networks